Madhani in Punjabi Poetry: An Analysis - Virk, Qaiser; Munawar, Sadia (sourcecoder, 2024)
The current study explores the significance and symbolic representation of the metaphorical concept of ’Madhani’ (churner) within Punjabi poetry. The study delves into how this traditional tool, used for churning butter, has transcended its literal meaning to embody various symbolic interpretations in the poetic landscape. Through an analysis of selected works, the study examines how poets have utilized ’Madhani’ to convey themes of struggle, transformation, and the process of extracting truth or essence from the complexities of life. The research also highlights the cultural, social, and philosophical dimensions embedded in the use of ’Madhani’ in Punjabi poetry, offering insights into the nuanced ways in which this metaphor enriches the poetic tradition. The study finds that Madhani has been employed as spiritual metaphor, representing the essence of hard work and struggle being showcased by the humans and the end product is reflective of human gain in Punjabi literature.